PESANTREN DI ERA DIGITAL ABAD 21 PERSPEKTIF RESTORASI MUHAMMAD ABDUH - Moh. Faizin; Afifah Amatullah Al Barru; Meirlyn Bunga Ambar Sari (STIT Al Mubarok Bandar Mataram - Lampung Tengah, 2022)
Islamic education is increasing with the times. Experts formulate and rearrange the structure of Islamic education, especially in the 21st century as it is today. Modern Islamic education is not just a transfer of knowledge but a foundation of faith and obedience. Therefore, what kind of Islamic educational institutions are in accordance with modern life like now. In this context the author aims to identify Islamic education in modern pesantren. The modernization of Islamic education is a form of renewal of the previous education system to achieve glory in the future and can give birth to an advanced Islamic civilization. The oldest educational institution in Indonesia, namely pesantren, is consistent in contributing to the socio-religious field to date. In this millennial era, all activities already use technology so that they can keep up with the times. This existing progress can be followed by one of the Islamic educational institutions, namely the Islamic Boarding School. In his perspective on modern Islamic boarding schools, Muhammad Abduh emphasizes that any learning at a given Islamic boarding school should use the discussion method because according to him reasoning power will be damaged if you always use the rote method.